2020
DOI: 10.1371/journal.pone.0231418
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between TERT promoter mutations and methylation culminates in chromatin accessibility and TERT expression

Abstract: The telomerase reverse transcriptase (TERT) gene is responsible for telomere maintenance in germline and stem cells, and is re-expressed in 90% of human cancers. CpG methylation in the TERT promoter (TERTp) was correlated with TERT mRNA expression. Furthermore, two hotspot mutations in TERTp, dubbed C228T and C250T, have been revealed to facilitate binding of transcription factor ETS/TCF and subsequent TERT expression. This study aimed to elucidate the combined contribution of epigenetic (promoter methylation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Interestingly, one study showed that TERTp hypermethylation was present in both melanoma and normal skin cells. However, only in melanoma cells with TERTp mutation did this hypermethylation correspond to increased TERT expression and chromatin accessibility ( 77 ). A further study by McKelvey et al.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Interestingly, one study showed that TERTp hypermethylation was present in both melanoma and normal skin cells. However, only in melanoma cells with TERTp mutation did this hypermethylation correspond to increased TERT expression and chromatin accessibility ( 77 ). A further study by McKelvey et al.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…The histone mark H3K27me3 maintains heterochromatin and recruitment of the polycomb repressor complex (PRC) for silenced genes ( 43 ). Alternatively, the H3K4me3 mark maintains actively transcribed genes in the open confirmation to enable access for transcriptional activators to bind ( 44 ). Telomerase negative primary cells exhibit high levels of the silencing H3K27me3 mark at the TERT promoter, compared to telomerase positive cancer cell lines ( 45 ), which exhibit the activating H3K4me3 mark ( 46 ).…”
Section: Tert Epigenetic Alterationsmentioning
confidence: 99%
“…In addition, we found that hTERT mRNA and protein expressions were increased in pTERTm melanoma cells, compared with nonmutated ones. However, several studies have demonstrated no correlation of hTERT protein expression with mutation status in tumoral tissues, thus suggesting that hTERT protein expression may be regulated by other mechanisms in addition to its promoter mutation [ 9 , 12 , 13 , 14 , 15 , 43 ]. The discrepancy in hTERT expression could be explained by the simplicity of the model used.…”
Section: Discussionmentioning
confidence: 99%